Technique of Dietary Supplementation of Guanidinoacetic Acid for Growth Improvement of Catfish (Pangasius hypophthalmus) - Aldi Huda Verdian; Rio Yusufi Subhan; Nurul Fatimah (University of PGRI Palembang, 2023)
The present study aims to determine the best technique of Guanidinoacetic acid (GAA) supplementation to improve retention of added GAA after immersion in water on the growth performance of Pangasius catfish (Pangasius hypophthalmus). Pangasius catfish juveniles with a mean body weight and length of 16.05 ± 0.47 g and 12.42 ± 0.30 cm were randomly distributed into 9 pond units (2 x 1 x 0,6 m). Three experimental diets were formulated to contain (0,5% kg-1 GAA) with different technique of GAA supplementation, i.e. control, pelleting technique and spray-coating technique fed to the fish for 60 days of culture. The results showed that average body weight and biomass of fish fed diet with by GAA supplementation with the pelleting technique was higher (p<0.05) than that of spray-coating technique and control. In conclusion, the consumption of diets containing GAA with pelleting technique resulted the best growth performance of Pangasius catfish (Pangasius hypophthalmus). Penelitian ini bertujuan untuk menentukan metode terbaik dalam suplementasi Guanidinoacetic acid (GAA) pada pakan untuk meningkatkan retensi penambahan GAA setelah perendaman di air dalam meningkatkan kinerja pertumbuhan ikan patin (Pangasius hypophthalmus). Benih ikan patin dengan rata-rata bobot 16.05 ± 0.47 g dan panjang 12.42 ± 0.30 cm dipelihara di dalam 9 unit kolam dengan ukuran (2 x 1 x 0,6 m). Ikan diberikan pakan selama 60 hari pemeliharaan tiga perlakuan yaitu; kontrol (tanpa penambahan GAA); perlakuan pelleting (penambahan 0,5% kg/GAA); dan perlakuan spray coating (penambahan 0,5% kg/GAA). Hasil penelitian menunjukkan bahwa perlakuan penambahan 0,5% kg/GAA dengan metode pelleting memberikan rata-rata bobot ikan dan biomasa paling tinggi dibandingkan dengan perlakuan lain dan kontrol (p<0.05). Kesimpulan dari penelitian ini adalah suplementasi GAA pada pakan ikan patin dengan metode pelleting menunjukkan kinerja pertumbuhan terbaik jika dibandingkan dengan metode spray coating pada ikan patin.